Global media convergence and cultural transformation emerging social patterns and characteristics - Jin, Dal Yong (Gale Virtual Reference Library, 2011)
Aims to engage the complex relationship between technology, culture, and socio-economic elements by exploring it in a transnational, yet contextually grounded, framework.